2010
DOI: 10.1007/s12032-010-9506-3
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of telomere length in human brain tumors

Abstract: Telomeres at the ends of human chromosomes consist of tandem hexametric (TTAGGG)n repeats, which protect them from degradation. At each cycle of cell division, most normal somatic cells lose approximately 50-100 bp of the terminal telomeric repeat DNA. Precise prediction of growth and estimation of the malignant potential of brain tumors require additional markers. DNA extraction was performed from the 51 frozen tissues, and a non-radioactive chemiluminescent assay was used for Southern blotting. One sample t-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Common germline variants in key telomere biology genes, RTEL1 and TERT, are associated with glioma risk [7-10]. Several studies have found a connection between telomerase levels, telomere heterogeneity, TERT promoter mutations and ALT in somatic glioma tissues and provide further evidence for a biological connection [14] [15-20]. A growing number of studies suggest that short germline RTL is a risk factor for certain cancers, including bladder, esophageal, gastric, head and neck, ovarian, renal and overall incident cancer[1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common germline variants in key telomere biology genes, RTEL1 and TERT, are associated with glioma risk [7-10]. Several studies have found a connection between telomerase levels, telomere heterogeneity, TERT promoter mutations and ALT in somatic glioma tissues and provide further evidence for a biological connection [14] [15-20]. A growing number of studies suggest that short germline RTL is a risk factor for certain cancers, including bladder, esophageal, gastric, head and neck, ovarian, renal and overall incident cancer[1].…”
Section: Discussionmentioning
confidence: 99%
“…Telomere length heterogeneity appears to be present in brain tumors. Some brain tumors appear to up-regulate telomerase whereas others maintain telomere length through the alternative lengthening of telomere pathway (ALT) [15-20]. The ALT pathway may play a role in specific subsets of glioma with mutations in Alpha Thalassemia/Mental Retardation X-linked (ATRX) and/or isocitrate dehydrogenase genes (IDH1) [18].…”
Section: Introductionmentioning
confidence: 99%
“…Given the critical role of MCPH1 in modulation of telomere repeat length, we analyzed the correlation between the MCPH1 promoter methylation and telomere length of each patients through southern blotting (Kheirollahi et al 2010). Significant association was found between MCPH1 promoter methylation and brain tumor's grade and stage.…”
Section: How Does Mcph1 Gene Behave In Brain Tumors?mentioning
confidence: 99%
“…The TL of all the patients, which was previously assayed [27], was statistically analyzed with ATM promoter methylation and clinicopathological features. In addition, status of TL was confirmed by Q-FISH which showed either severe lack or low intensity of signals (Fig.…”
Section: Telomere Lengthmentioning
confidence: 99%